(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The red sunrise, red sunset, and blue sky were common nature phenomena. Why sunrise and sunset are red color, and why daytime sky is blue? This paper used earth atmosphere refraction principles to explain the sky and sun color. The energy attract force equation was considered to explain the sun light offset at the outer atmosphere acted by earth mass, which may be better for understand the Relativity Theory. The conclusion will be benefit for the telescope application, satellites communication, astronomy observation, and other atmosphere optical applications.